Localização e Expressão da Angiotensina - (1-7) do Receptor MAS e da Enzima Conversora de Angiotensina tipo 2 em Leiomiomas Uterinos - Alexon Melgaço Racilan (2019)
LOCALIZATION OF ANGIOTENSIN- (1-7), MAS RECEPTOR AND ANGIOTENSIN TYPE 2 CONVERTER IN UTERINE LEYOMIOMAS AND MYOMETRIUM The "protective" axis of the renin-angiotensin system is composed by Angiotensin (Ang)-1-7, its receptor MAS, and the type-2 angiotensin converting enzyme (ACE2). This axis opposes the actions of Ang-II in many target tissues and biological functions. One of the well documented effects of Ang-(1-7) is to reduce lung and kidney fibrosis. Uterine fibroids are benign tumors with high prevalence and morbidity, whose histological features include collagen deposition and fibrosis. The aim of this study was to evaluate whether the main components of the Ang-(1-7) axis are present in human myometrium and uterine fibroids. Paraffin-embedded samples of uterine fibroids and normal myometrium were obtained from hospital files and processed by immunohistochemistry using specific antibodies to (Ang)-1-7, MAS and ACE2. The immunostaining was graded as absent, weak, moderate or strong by two independent observers. Negative controls had the primary antibodies replaced by non-immune serum. The mRNAs encoding MAS and ACE2 were assessed in another group of fibroid and myometrium samples using real time PCR. Ang-(1-7) was detected in the cytoplasm of smooth muscle cells with wide distribution and moderate intensity, both in normal myometrium and uterine fibroids. MAS receptor was present in both normal and fibrotic smooth muscle cells, with frequent nuclear localization. ACE2 was detected in normal myometrium and uterine fibroids, being particularly more concentrated in regions of higher cell density. Both MAS and ACE2 mRNAs were detected in fibroid and myometrium samples. This study firstly shows that human myometrium and uterine fibroids contain the full protective/antifibrotic axis of the renin-angiotensin system. The functional importance of this system for fibroid development remains to be investigated.